Inappropriate Cropping System: The Root Cause of the Poverty of Farmers in Shevgaon Tehsil of Ahmednagar District, Maharashtra. (International Journal of Food and Nutritional Sciences, 2022)
Agriculture has been practised in human society for 10,000 years. In order to ensure that there issufficient food production to suit the needs of the human population, farmers have been pushed to utilise"modernised" agricultural practises. All of these advancements are intended to produce crops that are moreresilient to environmental hazards, larger, mature more quickly, and are profitable. We are now able toproduce more on a given piece of land in less time because to the modern methods.Farmers in the study region, which is largely semi-arid, have recently adopted income crops likesorghum and millet due to the lack of land and water for cotton and onions. How farmers shouldimplement their agricultural strategy in light of the local terrain is the main focus of the current study.Basically, effective cropping, low cost of production and organic agriculture system are the major optionsif one wants to better their financial situation.According to analysis, we should choose 30% cash crops, 20% food grains, 20% pulses, 20%oilseed crops, and 10% fodder crops based on climatic condition and water availability. By maintainingtheir area-wise ratio, we can lower production costs and prevent the oversaturation of one crop in asignificant area.